English Language Proficiency, International Exposure, and Global Career Opportunities among Sport Science Students: Challenges and Pathways toward World-Class University - Zahrah Zakiya Ahda; Gustiana Mega Anggita; Mohammad Arif Ali; Radita Asti Prawita; Fanisa Dwi Nanda Sofia (ACPES Journal of Physical Education, Sport, and Health (AJPESH), 2025)
The internationalization agenda of higher education has become a critical component in achieving World-Class University (WCU) status. Within this context, English language proficiency plays a strategic role in preparing students to participate in international academic and professional environments. This study explores the perceptions, challenges, and expectations of Sport Science students regarding English language competency and its contribution to international exposure and global career opportunities. Using a mix-Methode approach, quantitative data were collected from 81 Sport Science students through open-ended surveys concerning their English language needs, learning experiences, and future career aspirations. while, 4 alumni were interviewed to get deeper context with workplace need. The findings reveal that students perceive English proficiency as essential for accessing international scientific literature, communicating in multicultural environments, participating in international sporting events, and expanding employment opportunities in the global sports industry. Students also recognize English as a crucial tool for obtaining international certifications, scholarships, and overseas professional experiences. However, several barriers remain prominent, including limited vocabulary mastery, difficulties in speaking and pronunciation, listening comprehension challenges, and insufficient confidence in academic writing. Students expect English learning programs to emphasize sport-specific terminology, practical communication skills, international academic literacy, and interactive learning methods aligned with professional sport contexts. This study proposes a conceptual pathway in which English language proficiency functions as a foundational competency that facilitates international exposure, which subsequently enhances global career opportunities for Sport Science students. The findings provide important implications for universities pursuing internationalization and WCU objectives by highlighting the need for discipline-specific English programs that support students’ global competitiveness and professional mobility.